CFD Simulation of Air-Piloted Downdraft Gasification Process: A Comparative Study Between Coal and Palm Kernel Shell as Feedstock - Mohd Dali, Mohd Amirul Mukminin; Abd Rashid, Razlin; Ishak, Izuan Amin; Mohd Salleh, Zuliazura; bin Madon, Rais Hanizam; Ishak, Mohammad Zulfikar; Samiran, Nor Afzanizam (International Journal of Integrated Engineering, 2023)
A fixed bed downdraft gasifier model based on computational fluid dynamic (CFD) framework was developed to investigate the influence of feedstock (palm kernel shell [PKS] and coal) on the quality of syngas produced via the gasification process. Euler–Euler approach was utilized in this study to describe the gas and solid phases. Realizable k-? turbulence model was used to evaluate the constitutive properties of the dispersed phase and the gas phase behavior. This simulation model was validated by comparing the syngas composition of gasification simulation of coal with previous research, which yielded the overall accuracy result of 83.2%. This study also highlighted that PKS gasification produced 53.74% and 90.51% higher composition of H2 and CO respectively as compared to coal gasification. Whereas coal gasification produced 81.35%, 71.31% and 52.29% higher composition of CH4, H2O and CO2 respectively as compared to PKS gasification. Hence, PKS produced 66.2% higher combustible gas of H2 and CO than coal. PKS is thus considered as a potential renewable feedstock for gasification process as an alternative to the non-renewable coal. In addition, PKS gasification produced 52.29% lesser composition of CO2 as compared to coal gasification.